2023
DOI: 10.1088/1612-202x/acc244
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the cytotoxic potential of Ficus palmata and its combination with chemotherapy and photodynamic therapy

Abstract: Ficus palmata (F. palmata) is a medicinally very rich plant that is used as a folk medicine to treat many diseases. This study investigated the anticancer effect of 70% ethanolic leaves extract of F. palmata alone and its combinational study with photosense-mediated photodynamic therapy (PDT) and doxorubicin hydrochloride (Dox-HCl) on rhabdomyosarcoma (RD) cells. The inhibitory dose (IC50) was calculated from dose response analysis of 24 h post exposure of F. palmata (400, 200, 100, 50, 25, 12.5 µg ml−1), Dox-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Dox-HCl in the presence of PS-PDT encourages singlet oxygen-dependent cytotoxic effects [ 59 ]. Outcomes of phase II clinical studies have shown considerable potential for the doxorubicin combination with additional chemo medicines for treating metastatic Rhabdomyosarcoma [ 60 , 61 ]. Photodynamic therapy has also been shown to have synergistic effects in the treatment of advanced pancreatic cancer [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dox-HCl in the presence of PS-PDT encourages singlet oxygen-dependent cytotoxic effects [ 59 ]. Outcomes of phase II clinical studies have shown considerable potential for the doxorubicin combination with additional chemo medicines for treating metastatic Rhabdomyosarcoma [ 60 , 61 ]. Photodynamic therapy has also been shown to have synergistic effects in the treatment of advanced pancreatic cancer [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has also been reported that photosense-mediated PDT improves therapeutic outcomes in conjunction with Dox [43] and DTIC [44] by simultaneously targeting DNA and proteins. Combining herbal or phytoproducts with synthetic medications promotes a beneficial synergistic impact, reduces drug resistance, and may reduce side effects [45][46][47].…”
Section: Discussionmentioning
confidence: 99%